The Syahādatain and the Conception of Obedience in Islamic Law - Waulil Amri; Reski Baskoro; Hudallah Hudallah (Penerbit Hellow Pustaka, 2025)
This study examines the role of Syahadatain as the fundamental basis of Muslim faith and its influence on the concept of obedience within Islamic Law in Indonesia. Syahadatain, consisting of the acknowledgment of Tawhid and the prophethood of Muhammad, is not merely a ritual statement but serves as an ontological, epistemological, and ethical foundation for individual behavior in worship and social transactions. The study employs a qualitative approach with library research, participatory observation, and in-depth interviews at pesantrens and Islamic educational institutions in Jakarta, Yogyakarta, and Surabaya. Findings indicate that internalizing Syahadatain fosters authentic obedience, enhancing moral integrity, honesty, trustworthiness, and spiritual awareness. Implementing Syahadatain values also has significant implications for public policy, character education, Islamic finance, and digital literacy in Indonesia. Major challenges include religious understanding diversity, fragmented educational authorities, modernity and secularism influences, limited resources, and resistance to pedagogical innovation. Strategies to strengthen obedience based on Syahadatain include revitalizing religious curricula, leveraging digital technology for education and da'wah, cross-sector collaboration, and developing role models among public figures. This study emphasizes that reinforcing Syahadatain can enhance individual and social integrity, support the development of a civilized, harmonious, and just society, and promote ethical and productive digital literacy.